Producing LIGA-competitive microcomponents - Hung, N. P.; Ali, Mohammad Yeakub; Yuan, S. (2000)
This paper presents a new technique to investigate deep microfeatures, and an alternative process to produce microcomponents. Micro-EDM and focused ion beam micromachining were combined to directly fabricate the mold features. The first process was to remove the bulk material while the later was to produce intricate details and improve the surface integrity. To investigate the effects of ion beam parameters on the mold material, nickel beryllium (Ni-Be) blocks were first ground, polished then mechanically clamped together. A focused ion beam using Ga+ ions was used to produce deep microfeatures at the block interfaces, after which the blocks were separated and the in-situ cross sections were examined. The parameters used were varied in the ranges of 30-50 kV accelerating voltage, 2-150 nC/μm2 dose, and 5-7000 pA beam current by either dry sputtering or gas-assisted etching. LIGA-competitive features were achieved. Selection of Ni-Be was made since its mechanical properties were superior to those of pure nickel used in the LIGA process. This ensured a longer mold life when one repeatedly injecting a hot/abrasive polymer to the mold cavity to fabricate three-dimensional microcomponents in production. Feature obtained with Ni-Be had surface finish ~10 nm, accuracy < 1 um, and aspect ratio >10. Preliminary work showed the success of this technique with micromolded plastics components.